2002
DOI: 10.1017/s0012162201002651
|View full text |Cite
|
Sign up to set email alerts
|

Developmental outcome, including setback, in young children with severe visual impairment

Abstract: This study retrospectively investigated the developmental perspective of 69 children (40 males, 29 females) with 'potentially simple' congenital disorders of the peripheral visual system: development was examined in the context of degree of visual impairment. Developmental and visual assessments were carried out at 10 to 16 months (Time 1) and 27 to 54 months of age (Time 2). Participants were grouped according to (1) visual status: profound visual impairment (PVI), severe visual impairment (SVI); (2) developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 33 publications
7
75
0
Order By: Relevance
“…The fit of the individual items to the Rasch measurement model is shown in Table I. Twenty-five of 29 items showed acceptable fit statistics (with the exception of items 5,6,12,13). A further indication of the appropriateness of the VISS items was the point measure correlations which indicated that all items, except for the misfitting ones, correlate well with the overall scale.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The fit of the individual items to the Rasch measurement model is shown in Table I. Twenty-five of 29 items showed acceptable fit statistics (with the exception of items 5,6,12,13). A further indication of the appropriateness of the VISS items was the point measure correlations which indicated that all items, except for the misfitting ones, correlate well with the overall scale.…”
Section: Resultsmentioning
confidence: 99%
“…The Rasch mathematical model is increasingly being used when assessing clinical measurement and quality of life tools. 14,16 Analysis showed acceptable fit of the scale and of the items to the Rasch model, except for four of the items (responds selectively to voices [5]; holds arms up to be lifted [6]; enjoys social play [12]; responds to being called by name [13]). Items 6 and 13 were underfitting (too unpredictable according to the Rasch model) and items 5 and 12 were overfitting (too predictable).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations